FAKTOR-FAKTOR PENYEBAB TERJADINYA PERKAWINAN DIBAWAH TANGAN DI SAMARINDA - Kartika Yanda (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACTIn the State of Indonesia marriage is an important issue for human life because it involves the future needs and personal, Religion and State. Regarding personal interests because they want to continue generation (offspring), concerning the interests of religion because marriage is a Worship or the Sunnah of the Prophet Muhammad (Islamic teachings).Marriage Act No. 1 of 1974 is to be thankful for the Indonesian Muslim community, because the Marriage Act is terjaminlah survival of Islamic law in Indonesia. With the Marriage Act of marriage approved by law and in addition it should be noted and registered, so that people do not go around again polygamy, divorce his wife, marry under the hand and so forth.